POLA PEMASARAN DAN KETERSEDIAAN PUPUK PASCA KEBIJAKAN PENGENDALIAN DISTRIBUSI PUPUK UREA MARET 2001 - NYAK ILHAM (SOCA: Jurnal Sosial Ekonomi Pertanian, 2002)
Free trade policy which is hope could avoid scarcity of fertilizer, at the end wascausing the condition of fertilizer scarcity. This condition push the government to replied thepolicy of urea control distribution. This research has an objective to evaluate the impact ofthese policy to marketing efficiency and fertilizer supply. Data and information was gatheredby using Rapid Rural Appraisal Method in some level of respondent in Kabupaten Subangand Garut on February 2001. The data was analysed by using description method with crosstabulation. The result of these analysis showed that the impact of urea control distributiongovernment supply with small variants of price. In the other way, for producer and tradersthis policy was give disincentive to them, but on the other hand their marketing systems quiteefficient. We still found some weakness factor which is caused the minimum function ofdealers/distributors, this all caused by unfairness between them. The indicate analysisshowed that comparable fertilizer use was not applied yet. To create sustainability infertilizer distribution, the unfairness should be eliminate. To control the price of fertilizercould be done as follows: (1) to push raw material price. In this case natural gases; (2) Todelete the obligation of Pusri in using storage in the Pusri fertilizer port; (3) to suggest valueadded tax 10 percent in fertilizer selling process, by this scenario we assumed that it willhelp them to use comparable fertilizer so the extension to farmer will keep continue.